Traditional Knowledge and Ethnobotany of Wild Plants from the Central Western Ghats, Karnataka, India - , Karthik H N; , Mahaboob Basha; , Chetan Bhanu Rathod; , Akshata Hegde; , Arvind B Rathod (Archives of Current Research International, 2025)
The study documents wild edible plants' diversity and ethnobotanical significance in the Sirsi region of Uttara Kannada, Karnataka. 73 wild edible species belonging to 41 families were recorded, with Lamiaceae and Myrtaceae being the most represented families. Among the surveyed species, Centella asiatica was the most frequently reported, followed by Murraya koenigii and Alternanthera sessilis. It highlights that leaves (36%) and fruits (34%) are the most commonly consumed plant parts, while seeds (10%) and tubers (9%) are used to a lesser extent. The majority of these wild edibles are native species (81%), while a small percentage are naturalized (9%) or introduced (10%). It is also revealed that a significant proportion of the respondents belong to the 31 to 40 and 41 to 50-years age groups, indicating that the ageing rural population primarily retains traditional ethnobotanical knowledge. Wild edible plants play a crucial role in local dietary habits, often consumed as tambuli, soup, or as ingredients in sambar. However, despite their nutritional and medicinal potential, these plants are not commercially exploited. Several species, such as Basella alba, Moringa oleifera, and Mimosa pudica, are reported to have medicinal uses, particularly in treating ailments such as vomiting, menstrual pain, and wound healing. The work emphasizes the importance of preserving and documenting indigenous knowledge related to wild edible plants. Given their nutritional, medicinal, and ecological significance, efforts should be made to promote their conservation and potential domestication. This research contributes valuable insights into the traditional uses of wild edibles and calls for further studies on their nutritional composition, propagation techniques, and sustainable utilization strategies.